2008
DOI: 10.1111/j.1471-0528.2008.01900.x
|View full text |Cite
|
Sign up to set email alerts
|

Women with obstetric fistula in Ethiopia: a 6‐month follow up after surgical treatment

Abstract: Objective To quantify surgical and quality of life outcomes 6 months after obstetric fistula repair.Design A prospective study. Women were examined and questioned at discharge and at follow-up appointment.Setting The Barhirdar Hamlin Fistula Centre, a dedicated unit treating women with obstetric fistula in northern Ethiopia.Population All women admitted to the Barhirdar Hamlin Fistula Centre suffering from vesicovaginal (WF) and rectovaginal fistulae (RVF).Methods All women were asked to return for a follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 15 publications
13
140
1
1
Order By: Relevance
“…8 In this study, loss to follow-up at 6 months was just under 40%, which is much lower than in our setting. Possible reasons for the very high losses to follow-up in our setting may be related to access, acceptability and/or fi nancial barriers.…”
Section: Public Health Action High Loss To Follow-up Among Fistula Pamentioning
confidence: 74%
See 2 more Smart Citations
“…8 In this study, loss to follow-up at 6 months was just under 40%, which is much lower than in our setting. Possible reasons for the very high losses to follow-up in our setting may be related to access, acceptability and/or fi nancial barriers.…”
Section: Public Health Action High Loss To Follow-up Among Fistula Pamentioning
confidence: 74%
“…Such outcomes are generally reported to be good, with fi stula closure rates of 73-93% reported from various other African settings, [13][14][15][16][17] compared to 87% in our setting. However, repair breakdowns are known to occur in the 6-month post-operative period, 8 invalidating these hospital discharge outcomes. Given the sequelae that can ensue after fi stula repair, we would emphasise the importance of implementing a system of cohort monitoring of all patients who undergo obstetric surgery for fi stula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those who have undergone surgical repair, health-related quality of life (QOL) is a key issue; however, most studies conducted to date have focused on QOL before rather than after surgery [4,5,7]. In the studies that have assess postsurgical QOL [6,[10][11][12], surgery has been shown to improve social life, physical activity, and psychological condition. However, some women who underwent obstetric fistula repair remained incontinent [10][11][12], and other health problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of RVF in developing countries is still obstetric injuries [1,2] with others being operative trauma, radiation injury, inflammatory bowel disease (mostly Crohn's disease), infection and cancer. RVF may be accompanied by considerable social, psychological and sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%